Optimum concentrations of potassium and zinc for better performance, nutritional, and biochemical quality of hydroponically cultivated Spinacia oleracea Cv. Virofly - Farhad Behtash; Raana Ramezani; Hanifeh Seyed Hajizadeh; Ghasem Eghlima (Scientific Reports)
Abstract In order to evaluate micro and macronutrient balance in vegetable growth, a study on greenness, yield, nutritional value, as well as biochemical status in spinach, has been conducted in a greenhouse, utilising the different concentrations of zinc (Zn) and potassium (K) in the nutrient solution. So, three concentrations of Zn (0.22, 5, and 10 mg L− 1) and K (39, 78, and 117 mg L− 1) were applied to hydroponically grown spinach (Spinacia oleracea cv. Virofly) through a factorial experiment based on a randomized complete design with three replications. The results showed that along with increasing concentrations of Zn and K in a nutrient solution, chlorophyll index and plant performance were increased although Zn showed more influence than K. The maximum plant yield was observed at 117 mg L− 1 of K in combination with both concentrations of Zn (5 and 10 mg L− 1). Along with an increase in Zn and K concentrations, the amount of nutrients including Na, Fe, Cu, Ca, Mn, and Mg decreased compared to the control level of Zn and K in nutrient solution except for Zn and K, which increased due to the Zn and K, respectively. Increased levels of Zn and K caused to decrease in malondialdehyde (MDA) content by 51% and 34%, respectively. Hydrogen peroxide (H2O2) was decreased also by 29% and 14% at 10 and 117 mg L− 1 concentration of Zn and K while higher levels of Zn and K in the nutrient solution, increased protein content by 1.4 and 1.2 folded compared to the control plants. The maximum activity of superoxide dismutase (SOD) was recorded in spinach treated with 10 mg L− 1 of Zn in combination independent to the K concentrations. The activity of ascorbate peroxidase (APX) was also affected by Zn as it showed up to 2.1 folded increment at 10 mg L− 1 Zn compared to the 0.22 mg L− 1 concentration. In general, an increase in Zn and K concentration in the nutrient solution decreased the absorption of measured nutrients except for Zn and K in spinach leaves. The effect of increased levels of Zn was more obvious than that of potassium in qualitative and biochemical traits of spinach specially at 5 mg L− 1 concentration. These findings suggest that supplementing hydroponic nutrient solutions with 5 mg L− 1 Zn in combination with 78 mg L− 1 K can lead to the better quality and tolerance of the plant, offering a promising strategy to enhance crop productivity and nutritional value in hydroponically cultivated spinach.